A Conceptual Framework for Technology Integration in Residential Architecture - Kiki Maria; Fauziyah; Keti Andayani; Iskandar Zulkarnain (Fakultas Teknik Universitas Pancasila, 2026)
Modern residential housing planning faces substantial complexity, spanning regulatory compliance, diverse user preferences, and demands for resource efficiency and sustainability. These challenges are often magnified by insufficient coordination, resulting in inefficiencies and potential errors. Through a purposive literature review, this study addresses a critical gap in the literature regarding conceptual frameworks that integrate architecture and information systems, particularly during the residential planning phase. Information System (IS) integration has become essential, enabling holistic building data management, analysis, and design optimization. Although technologies such as Building Information Modeling (BIM) and Decision Support Systems (DSS) are widely recognized for their potential, existing studies emphasize specific technologies or practical implementations, leaving a need for a more abstract and foundational integrative model. This study develops an innovative conceptual framework model depicting the essential synergy between architectural design principles and information systems capabilities to optimize the planning process. The proposed model positions information systems as the main enabler, supporting data management, analysis, and visualization through an Integrated System that combines BIM, DSS, and the Internet of Things (IoT), producing data-driven, collaborative, and optimized planning outputs. This framework provides a theoretical foundation for future interdisciplinary research in technology-driven residential planning.